Developing a new hysteretic type seismic damper (BRRP) for steel bridges. (1st October 2016) - Yamazaki, Shinsuke; Usami, Tsutomu; Nonaka, Tetsuya
Highlights: A new type of high performance seismic damper (BRRP) for steel bridges is developed. BRRPs possess both high deformation and high low-cycle fatigue performances. The superiority over conventional BRB dampers is demonstrated by test and analysis. Abstract: New seismic dampers termed Buckling-Restrained Rippled Plate (BRRP) dampers have been developed. The BRRP dampers are similar in shape to BRB (Buckling-Restrained Brace) dampers, but its core member is a 2D rippled plate instead of a 1D narrow flat plate. BRRPs are intended to be used as stoppers, and when they are installed at the edges of girder-type bridges, they will act as stiff elastic bearings in small to moderate earthquakes (called "Level 1 earthquakes" in Japan) and as energy dissipating dampers in large earthquakes (called "Level 2 earthquakes" in Japan). The target performance of BRRPs is such that they can withstand earthquakes exceeding Level 2 earthquakes (say, 1.5 times larger than a Level 2 earthquake). The inelastic behavior of BRRPs was investigated using both cyclic loading tests and numerical analyses to acquire fundamental knowledge on their performances. It has been found that adequately designed BRRPs exhibit much better deformation and low-cycle fatigue performance than conventional BRBs.